ANTHROPOMETRIC MEASURES IN PATIENTS WITH CEREBRAL PALSY IN CHILDREN WELFARE TEACHING HOSPITAL IN BAGHDAD - Dr. Zuhair Saleh Farhan; Dr. Abbas Mohsin Younus; Dr. Hala Abdul Khalak yahea; Dr. Ali Qais Abdulkafi (Web of Journals Publishing, 2025)
Background: Among children, cerebral palsy accounts for the vast majority of physical impairments. Children who have cerebral palsy (CP) can experience secondary health issues, such as growth and nutrition difficulties. Patients & methods: One hundred children with cerebral palsy, ranging in age from six months to forty-eight months, who were either seen in the neurology clinic or admitted to the neurology ward at Children Welfare Teaching Hospital between January 1, 2010, and September 30, 2011, were the subjects of this cross-sectional study. The anthropometric measures used for nutritional assessment included height, weight, skinfold thickness, mid-arm circumference, and body mass index. Results: There were 56 men and 44 females among the 100 cases of cerebral palsy. Of all the cases, 78 patients were of the spastic type; 54 of those were of the SQCP type; and the remaining cases were of less common forms. There were 13% of cases under -2 SD and 54% under -3 SD based on weight for age. By far, the subtype most impacted is SQCP. Of all the instances, 18% had a length or height that was less than -2 standard deviations, and 51% were shorter than -3 standard deviations. The SQCP subtype suffered the most. In terms of weight for length/height, 17% of the instances fell below -2 standard deviations, while 26% fell below -3 standard deviations. The SQCP subtype suffered the most. Eighteen percent of the cases had a body mass index (BMI) below -2 SD, and thirty-four percent fell below -3 SD. The SQCP subtype suffered the most. When adjusted for age, 23% of cases had a mid-arm circumference that was less than -2 standard deviations, and 46% had a mid-arm circumference that was less than -3 standard deviations. The SQCP subtype suffered the most. With age, the triceps skin folds. Only 15% of instances fell below -2 SD, while 25% fell below -3 SD. The SQCP subtype suffered the most. Conclusion: Cerebral palsy is associated with an increased risk of malnutrition. People suffering from CP showed changes in all of the anthropometric measures. The most impacted subtype was SQCP, while the most impacted type was spastic. Clinical trials have shown that anthropometry is an accurate tool for evaluating dietary intake. Aim: Using anthropometry, we wanted to find out how well children with cerebral palsy (CP) were eating. Determine the type of CP most affected by malnutrition and demonstrate this to them.
Keywords: Cerebral palsy (CP), brain lesion, Anthropometric measurements classification.